Simultaneous impact modified and chain extended glass fiber reinforced poly(lactic acid) composites: mechanical, thermal, crystallization, and dynamic mechanical performance - Akindoyo, John Olabode; Beg, M. D. H.; Suriati, Ghazali; Heim, Hans P.; Feldmann, Maik; Mariatti, M. (John Wiley and Sons Inc., 2020)
Herein, glass fiber (GF) reinforced binary, ternary, and quaternary poly(lactic acid) (PLA) composites were prepared. Toughening, and chain extension of PLA was achieved through the incorporation of impact modifier and chain extender and their concurrent effects on the spectroscopic, crystallization, mechanical, thermal, and thermomechanical properties of the composites were investigated. High mechanical properties of GF influenced the mechanical performance of the composites. However, GF alone could not restrict the chain mobility of PLA due to poor interface and low crystallization activities in the PLA‐GF composite. Incorporation of impact modifier and chain extender produced significantly enhanced interaction between GF and PLA. Significantly, the crystallinity, impact strength, and flexural modulus of PLA in the quaternary composite were increased by 58%, 63%, and 66%, respectively. In addition, damping and effectiveness coefficient of the PLA‐GF composite were notably reduced by the simultaneous impact modification and chain extension of the reinforced composites.